Métodos de otimização de redes de distribuição de água - Lino, Jhonatan Brunno Ferreira da Silva (2021)
This work aims to present a computational model for optimization in water distri bution networks, where the main objective is to minimize the cost. This study starts from a hydraulic balancing, resulting from a system of non-linear equations, where the parameters of the network are defined. The network will be created through the Epanet program, and the results obtained in this process will be presented by Lenhsnet (network optimization module of the Epanet program). The other model is developed from the Hansen, Madsen and Nielsen method, through fmincon, tool from matlab. Simulations will be carried at some example of network, varying the optimization method used, and verifying which one of these methods presents better results in relation to convergence and processing time.